STRUCTURE, LINGUISTIC STRUCTURE OF DISCUSSION SPEECH - A. Dadajonov (Modern American Journals, 2025)
The article analyzes the interpretations of the concept of “structure” in linguistics and the formation of structural linguistics, with particular emphasis on the linguistic structure of argumentative discourse. Based on the theoretical views of I.A. Baudouin de Courtenay and F. de Saussure, the importance of the structural approach in revealing internal relations between language elements is highlighted. The study examines the compositional structure of argumentative discourse, including thesis, argumentation, and conclusion, as well as linguistic means used to express cause-and-effect relations. The research substantiates that argumentative discourse is not only a logical category but also a linguistic one with a specific semantic and structural organization.
Keywords: Structure, structuralism, argumentative discourse, types of speech, thesis, argumentation, conclusion, cause-and-effect relations.